Analysis of Farmer’s Group Functions in the Adoption Process of Superior Seed Innovation in Waimital Village, Kairatu District - Damanik, Inta P. N.; Tahitu, Meilvis E.; Kembauw, Esther (International Journal of Multidisciplinary Sciences and Arts, 2023)
The objective of this research was to analyze the function of farmer groups in the process of adopting superior seed innovation in Waimital Village, including Inpari Sidenuk. The research was conducted in Waimital Village as one of the centers of rice production in Maluku. The research population was all farmer groups who participated in the trial of planting superior seeds of Inpari Sidenuk, there were 11 groups and all of groups was taken as sample with 82 farmers as group member.  The data were analyzed using a simple statistical test, namely cross tabulation and then was interpreted according to the research objectives. The results showed that according to the farmers the function of farmer groups (as a vehicle for learning and for collaboration) was useful in general, but in making the decision to adopt or not to adopt a superior seed, including Inpari Sidenuk, there was no farmer group involvement. Each farmer was free to decide whether or not to adopt the new superior seeds. After the trial planting, the majority of farmers did not adopt seeds of Inpari Sidenuk because they worried about the availability of the seed and other production facilities and the difficulties to sell the yields. These worries should be anticipated by farmer groups by increasing the capacity of farmer groups as a vehicle for learning and collaboration.  For example, making farmer groups as "farm shops" and as "farm product marketing agents". For this, it is necessary to make improvements of farmer group management, make cooperation with distributors of agricultural production facilities and with product buyers.  Another thing is to keep quality, quantity, and continuously product.